KOI HERPES VIRUS SEBAGAI PENYEBAB KEMATIAN MASSAL Cyprinus carpio koi DI INDONESIA [Koi Herpes Virus the Causative Agent of Sporadically Mortality of Cyprinus carpio koi in Indonesia] - Madyowati, Sri Oetami; Sumaryam, Sumaryam; Kusyairi, A; Suprapto, Hari (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Virus was isolated from infected koi Cyprinus carpio koi with KHV and confirmed by polymerase chain reaction (PCR) and transmission electron microscope (TEM). Fish that were naturally living near koi pond such as catfish Clarias batrachus, nila Oreochromis niloticus, koki Carrasius auratus, and komet Macropinna microstoma did not infected after the cohabitation test. Based on the results KHV was the agent responsible for mortality of million cultured koi in East Java Province Indonesia. Absolute mortality was occurred in koi between 48-72 h post infection, while other cyprinids family was not caused in mortality. Other fresh water fish such as catfish Clarias batrachus, nila Oreochromis niloticus, koki Carrasius auratus, and komet Macropinna microstoma was not infected. Virus-like particles as found in gill ofinfected fish with KHV.